A Legal Analysis of the Status and Protection of Unsecured Creditors in Bankruptcy Proceedings Under Law No. 37 of 2004 on Bankruptcy and Voluntary Debt Restructuring - Marsaulina Br Siagian; Herman Brahmana (Green Publisher Indonesia, 2026)
This research discusses the legal position and legal protection of concurrent creditors in bankruptcy proceedings under Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (Penundaan Kewajiban Pembayaran Utang/PKPU). Concurrent creditors are creditors who do not hold special guarantees or privileged rights and are therefore placed last in the order of bankruptcy asset distribution. In practice, concurrent creditors often suffer losses because the debtor's assets are insufficient to cover all debts after secured creditors and preferred creditors have been paid first. This research aims to analyse the legal position, normative protection, and the obstacles faced by concurrent creditors under Law No. 37 of 2004, along with proposed solutions. This research employs a normative legal research method incorporating statutory, conceptual, and case-based approaches. Legal materials were obtained from laws and regulations, books, journals, and court decisions related to bankruptcy. The results of the study show that the legal position of concurrent creditors is recognised under Articles 1131 and 1132 of the Indonesian Civil Code (Kitab Undang-Undang Hukum Perdata/KUHPerdata) and Law Number 37 of 2004. Concurrent creditors hold the right to submit claims, attend creditors' meetings, and receive a proportional distribution of bankruptcy assets. However, legal protection for concurrent creditors in practice remains ineffective due to the dominance of secured creditors, high bankruptcy costs, a lack of transparency in the management of bankruptcy assets, and inadequate supervision of kurator (bankruptcy trustees).